Performance Evaluation of Money Market Mutual Funds in Greece - Galetsas, Ioannis (2008)
The present study attempts to evaluate the performance of money market mutual funds in Greece and the factors that are affecting it. The analysis showed that money funds tend to under-perform the market and that the return is negatively related to expenses but positively related to size of the fund. However, higher expenses can lead to better performance if they are used to attract better quality managers and also high size seems to reduce performance, probably due to diseconomies of scale.